The functionality of fiber bragg grating sensor compared to that of foil gaug - Ahmed Tahir, Bashir; Ali, Jalil; Abd. Rahman, Rosly (Science Publications, 2005)
Technology such as fiber Bragg grating (FBG) sensors are widely accepted in almost all industries. FBG are being investigated for their applicability in other markets such as smart structures. Fiber optic sensors can also be used in many different applications. Fiber optic sensors are available in several types; among them, the Bragg grating sensor is being studied in this research. For this research work, the main focus was the use of fiber Bragg grating sensors for measuring strain. The key objective of this research; to determine the functionality of fiber Bragg grating sensors compared to that of conventional foil gauges. Fiber Bragg grating sensors were chosen for this research because they have a high potential for various uses in the monitoring of smart structures. The major incentives for this type of research are the current deterioration of civil structures in west Malaysia. The laboratory tests are being reported in this research work including tests of steel straps and an aluminum test specimen. In all the tests, strain was measured using the fiber Bragg grating sensors and compared to values from a conventional foil gauge. The results are being discussed in details. It was inferred that the use of fiber optic technology for the monitoring of civil structures is very promising and the future is sure to bring further advancements and improvements.